Self-regulation versus habit: the influence of self-schema on fruit and vegetable consumption - Allom, Vanessa; Mullan, Barbara (Routledge, 2012)
The aim of this study is to examine the determinants of fruit and vegetable (F&V) consumption with the application of the Theory of Planned Behaviour (TPB) and the additional variables of self-schema, habit and self-regulation. While it has been shown that those with a healthy-eater self-schema are more likely to carry out their healthy dietary intentions, the underlying processes that influence this relationship have received limited empirical attention. Recent findings on dietary behaviour suggest that self-regulatory ability and habit strength may have dissimilar effects on the intention–behaviour relationship within schematics and non-schematics. Self-report questionnaires regarding F&V consumption cognitions and two tests of self-regulation were administered to 209 university students. One week later, participants completed questionnaires on their behaviour. The TPB significantly predicted intentions and prospective behaviour. Self-schema did not moderate the relationship between intention and behaviour. However, within healthy-eater schematics, those with high intention and high self-regulatory ability were more likely to consume F&V, while within non-schematics, those with low intention and high habit strength were more likely to consume F&V. The findings support the use of the TPB in predicting F&V consumption and the validity of the self-schema distinction. Implications for designing interventions are discussed.